Causes of gender inequality in Saudi Arabia with focus on social and religious factors - Pichugina, Ekaterina; Sejkora, Jiří, 1985-; Mazánková, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis investigates the multifaceted causes of gender inequality in Saudi Arabia, with a focus on social and religious factors and their interrelation. The research employs a comprehensive approach to analyze the historical, cultural, religious, and sociopolitical aspects that contribute to gender inequality worldwide, and then applies these aspects specifically to the case of Saudi Arabia. The work relies on various indices, such as the Gender Inequality Index (GII), the Global Gender Gap Index (GGI), and the Social Institutions and Gender Index (SIGI), to assess the current state of gender inequality in Saudi Arabia. The study highlights the development of gender inequality in various spheres of women's lives in Saudi Arabia and recent trends. The results underscore the complex interaction between religion and social institutions, demonstrating how Wahhabi interpretations of Islamic texts affect the social status of women. The thesis also examines the role of social institutions such as the family, education, and the state in maintaining gender stereotypes and limiting women's opportunities. By comparing social and religious influences, the research aims to identify the main drivers of inequality in Saudi Arabia.
Vedoucí práce: Jiří Sejkora
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses